Preliminary validation of Mycobacterium tuberculosis complex-specific PCR tests for the detection of M. bovis and M. tuberculosis in formalin-fixed, paraffin-embedded tissues of captive and free-ranging wildlife - Michel, Anita Luise (University of Pretoria, 2014)
Dissertation (MSc)--University of Pretoria, 2013.